Pengaruh Kinerja Pasar dan Kinerja Fundamental Terhadap Harga Saham (Studi Kasus PT Bank Rakyat Indonesia, Tbk) - Armis Pandanan; Nely Salu Padang (Journal of Financial and Tax, 2021)
This study aims to determine the significance of pbv and roe influence indirectly on BBRI's share price. This study uses an associative approach. The associative approach aims to determine the indirect influence of PBV and ROE on BBRI's share price. Data collection techniques performed by researchers is to perform documentation techniques and library studies. The analysis tools used in this study used path analysis with the help of SPSS 22. Based on the results of the analysis conducted, the results showed that PBV indirectly has an insignificant effect on the share price of BBRI and ROE indirectly has a significant effect on the share price of BBRI